MOLECULAR DETECTION OF SERRATIA MARCESCENS ISOLATED FROM DIFFERENT CLINICAL CASES IN WASIT PROVINCE, IRAQ - Salim , Walaa Medhat Salim; Al-bayati , Luma Hikmat (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
TEST